Strategi Pengembangan Pariwisata Di Indonesia - Soebagyo Soebagyo (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2012)
Tourism has provided considerable foreign exchange in many countries. Tourists visit will stimulate social interaction with people around the major tourist attractions in adapting well in the field of economy, society and culture. The positive impact of tourism activities in the field of economics, namely the State foreign exchange income. Tourism development has three functions: to promote economic, preserve national identity and the preservation offunction and quality of the environment, and fostering a sense of patriotism and the nation. Because it needs to be developed as well as increased marketing and promotion of tourism education and training. Very significant contribution of tourism for job creation. Tourism needs to develop new tour packages such as agro-tourism or ecotourism. Society needs to be given the opportunity to market local products and help them to the skills and the provision of capital for businesses that bring in profits.